DETERMINANTS OF FACTORS RELATED TO NUTRITIONAL STATUS IN HIGH SCHOOL STUDENTS - I Putu Sudayasa putu; Asmarani rani; Nurzulifa nur; Widyawati Samita widya; La Ode Alifariki riki (STIKes Hang Tuah Pekanbaru, 2019)
Background: Nutritional status is a condition caused by the balance status between the amount of intake (intake) of nutrients and the amount of nutrients needed by the body for biological functions, such as physical growth, development, activities, health maintenance, and others. Objective: this study aims to determine the determinants of factors related to student nutritional status. Method: This study uses a cross sectional research design. The research sample amounted to 121 respondents. Data were taken using the International Physically Actual Questionnaire (IPAQ) questionnaire, using the questionnaire consumption pattern of poke shells, Food Frequency Questionnaire (FFQ), digital stamp balance, and microtoice. Data analysis consisted of univariate and bivariate analyzes using spearmen statistical tests of p value <0.05 and correlation coefficient (r). Results: The results showed that there was no relationship between physical activity (p = 0.085), fat consumption patterns (p = 0.944), pokea shell meat consumption patterns (p = 0.078) with nutritional status in class XI students of SMAN 1 Sampara in Sampara District. Conclusion: The conclusion of this study is that there is no relationship between physical activity, fat consumption patterns and meat of pokea shells and nutritional status in class XI students of SMAN 1 Sampara in Sampara District.